Social Media And Hoax In Political Communication - Afifuddin Harisah (Journal of Research and Multidisciplinary, 2020)
Since the United States of America presidential election in 2016, the spread and use of hoax on social media, in addition to hate speech, in modern politics to seek public support proven to be far more critical than the spread of real news in media. What needs to consider is social unrest between Muslim and civil society that may occur because of the range of hoax. Social media that should be a means to increase ukhuwah becomes a means to destroy the pluralistic social relations of a nation. Political communication, especially in Indonesia ahead of the presidential election in 2019, cannot be separated from the rampant of hoax reports from both sides of the presidential election candidates. This research is a qualitative descriptive study that aims to understand the perspective of the Quran and university students on the use of hoax on social media for political purposes